Creative Nonfiction Pedagogical Framework Analysis - Miriam Barton (The Advocate, 2026)
This pedagogical framework analysis delineates the role of creative nonfiction writing instruction and its place within expressivism, social cognitive theory, and self-determination theory. It also explores pedagogical approaches in response to the gross lack of importance currently placed on creative writing learning, for ELA students and preservice ELA teachers alike. Emphasis is placed on the experience of learning the craft within classroom communities and alongside supportive instructors as well as the concepts of diversity of thought and freedom of expression. Creative nonfiction writing in the classroom quintessentially manifests concepts of autonomous learning.
Keywords: creative writing pedagogy; autonomous learning; expressivism; narrative writing; classroom writing community; self-determination theory; social cognitive theory